Impact of the Creative Parenting Parenting Program - Ratzlaff, Harold C.; Friesen, John D.; Neufeld, Gordon; Paddick, Gael M. (Canadian Journal of Counselling and Psychotherapy, 2011)
Seventy parents volunteered to participate in a program called Creative Parenting. A Solomon four-group design was used to register change on measures related to program content. Two of the five measures resulted in statistically significant gains. The results supported the proposition that the Creative Parenting program was effective in changing parental behaviours on two dimensions. Parents became more accepting of their children and relied less on parental authority in their relationship with their children.